Aqui, todo mundo é da mesma família : parentesco e relações étnicas entre os ciganos na cidade alta, Limoeiro do Norte CE - Silva, Laílson Ferreira da (2010)
This study aims to understand how facing a context of Constant interaction whit the local population, the gypsies family Alves dos Santos, neighborhood residentes in uptown, Limoeiro do Norte Ce, maintain a sense of ethnic belonging. To that end, I analyze both the social relations between Gypsies and non-gypsies community, as it is from the contact that the social boundaries are delineated, as the discourses and social representations that are used to qualify them from stigma. So, I found that grounded in the notion of family, gypsies are seen as a group, searching the history / past nomadic origing and blood common elements that underlie its condition, and the language a cultural trait that makes it possible to establish objective distinctions among gypsies and other community residentes, becoming thus a diacritical mark.